A Linear and Non-Linear Causality Analysis between Military Expenditures and External Debt in NATO Member Countries - Karagianni, Stella; Pempetzoglu, Maria (European Journal of Economics and Business Studies, 2019)
This paper deploys the linear and non-linear Granger causality methods in order to determine the causal relationship between military expenditures and external debt in NATO countries for the time period 1960-2015. Its innovative feature lies in the empirical application of the Francis et al. (2010) nonlinear causality test. To our knowledge, this is the first study to employ the specific test in order to explore the existence of potential nonlinear links between military spending and debt. The empirical results indicate the existence of linearity in the cases of Greece, Italy, UK and USA and the existence of nonlinearity in the cases of Turkey and USA. The paper aims to provide valuable input to the regulators and decision makers.